Perancangan Sistem Penggerak 2 Axis Pada Sel Surya Berbasis Sensor Matahari - Arif Gunawan; Rizki Dian Rahayani (UIN Sultan Syarif Kasim Riau, 2015)
Sunlight is a potential renewable energy source. Located at the equator, Indonesia is very potential to generate solar energy in large amounts, where the sun's rays are received per day to reach 4.5 KWH per square meter. But amount of solar energy produced by the solar cell device, is depend on panels position and its tilt follow the sunlight position. In order to absorb solar energy maximally, it would require an active driving tool, which can move the panels follow the direction of sun's movement. Its condition is the background of this research. In this research, we will design an 2 axis rotator based on a solar sensor (mini solar cells) as solar tracker, which can move the solar cell panels, up and down, right and left follow the direction of the highest intensity of sunlight. Then, this mechanical system will be implemented on an adaptive solar cell panel systems, which will be discussed on further research. From the initial measurement, it is known that the reference voltage on the mini solar cells which is used as panels direction is 39.17 V. Where the driving system will be stopped at a certain position when the voltage on mini solar cells has same value with the reference voltage. The rotator power consumption of each movement on each axis, for a 80 Kg weight load is 84 W.Keywords: 2 Axis Rotator, Solar Cell, Solar Tracker